Immune responses in pigs and cattle vaccinated with half-volume foot-and-mouth disease vaccine - Park, Min-Eun (J Vet Sci, 2017)
With the current commercial foot-and-mouth disease vaccine, inoculating twice increases the formation of denatured meat due to granuloma or residual adjuvant at the injection site in pigs, resulting in economic loss. Therefore, we investigated protective antibody levels after reducing the amount of adjuvant in the vaccine. Field applicability of the experimental vaccine, made with a new adjuvant ISA 201, was tested by vaccinating farm animals with half-volume doses (1 mL/animal) of commercial vaccine and monitoring their immunogenicity. Among pigs, the group that received a half-volume dose showed similar or higher titers of structural protein antibody and neutralizing antibody than those receiving the standard dose (2 mL). In pigs, the durable effects of antibody titer of the reduced vaccine volume did not diminish up to the time of slaughter. Among cattle, boosting with a second 1 mL vaccine increased virus neutralizing antibody for the protective effects. The boosting effects were more marked in cattle than in pigs. The immune responses differed between species with the effect of the half-volume vaccination being lower in cattle than in pigs. In conclusion, the immune response to the half-volume vaccine was similar to that from the standard volume vaccine in pigs, but not in cattle.